Hidrolisis Kadar Glukosa Kertas Koran Menggunakan Gelombang Ultrasonik - Fitria Fitria; Karim Kasmudin (STTI Bontang, 2022)
Abstract Newspaper is one of the mass media that is often used by the public but has the potential to produce the most dominant paper waste. Based on data from the Balikpapan Kaltim Tribune in 2016, the number of printed newspapers for the province of East Kalimantan reached 635,538 tons per year. Based on the dry substrate, newspaper contains 42.2% cellulose; 24.85% hemicellulose and 23.07% lignin which can be utilized and have higher economic value when hydrolyzed into glucose in the manufacture of bioethanol. This study aims to determine the optimum temperature and time of the ultrasonic wave-assisted newspaper hydrolysis process. This research was carried out by hydrolyzing 100 grams of newspaper powder and dissolved in 600 ml of 1% H2SO4 using 28kHz ultrasonic waves with temperature variations (60°C, 70°C, 80°C and 90°C) and time variations (10 minutes, 20 minutes). , and 30 minutes). The resulting glucose was analyzed using the Luff Schoorl method. The results of this study showed that the highest glucose level of 2.3994 mg/g was obtained at a temperature of 80°C and a hydrolysis time of 10 minutes. Keywords: glucose, hydrolysis, newsprint, ultrasonic